Pharmacological preconditioning with the cellular stress inducer thapsigargin protects against experimental sepsis. (March 2019) - Wei, Yaping; Meng, Mei; Tian, Zhenyu; Xie, Fubo; Yin, Qihui; Dai, Chaochao; Wang, Jingjing; Zhang, Qunye; Liu, Yu; Liu, Chang; Yan, Feng; Jiang, Fan; et al.
Graphical abstract: Abstract: Previous studies have shown that pretreatment with thapsigargin (TG), a cellular stress inducer, produced potent protective actions against various pathologic injuries. So far there is no information on the effects of TG on the development of bacterial sepsis. Using lipopolysaccharides- and cecal ligation/puncture-induced sepsis models in mice, we demonstrated that preconditioning with a single bolus administration of TG conferred significant improvements in survival. The beneficial effects of TG were not mediated by ER stress induction or changes in Toll-like receptor 4 signaling. In vivo and in cultured macrophages, we identified that TG reduced the protein production of pro-inflammatory cytokines, but exhibited no significant effects on steady state levels of their transcriptions. Direct measurement on the fraction of polysome-bound mRNAs revealed that TG reduced the translational efficiency of pro-inflammatory cytokines in macrophages. Moreover, we provided evidence suggesting that repression of the mTOR (the mammalian target of rapamycin) signaling pathway, but not activation of the PERK (protein kinase R-like endoplasmic reticulum kinase)-eIF2α (eukaryotic initiation factor 2α) pathway, might be involved in mediating the TG effects on cytokine production. In summary, our results support that pharmacological preconditioning with TG may represent a novel strategy to prevent sepsis-induced mortality and organ injuries.